Effects of different drugs in combination with PKP/PVP on postoperative pain in patients with osteoporotic compression fractures: a network meta-analysis - Bai, Yiguang; Chen, Qiaoling; Wang, RouMei; Huang, Rui (Frontiers in Surgery, 2024)
Objective This study was designed to evaluate the postoperative pain effect and clinical efficacy of different drugs combined with PKP or PVP in treating osteoporotic vertebral compression fractures (OVCFs) through a systematic review and network meta-analysis. Methods We searched five electronic databases, namely, MEDLINE (PubMed), EMBASE, Web of Science, Google Scholar, and the Cochrane Central Register of Controlled Trials online, for the treatment of OVCFs through March 2023 with keywords zoledronic acid (ZOL), teriparatide (TPTD or PTH 1-34), and calcitonin (CT) combined with PKP/PVP. The visual analog scale (VAS) and Oswestry Disability Index (ODI) were the primary outcomes of the network meta-analysis, and the secondary outcome was the diagnostic marker bone mineral density (BMD). Results Eighteen studies involving 2,374 patients were included in this study. The network meta-analysis revealed that, in terms of reducing VAS scores, compared with PVP surgery alone, PVP combined with TPTD was most likely to be the treatment associated with the greatest pain relief [MD = −4.99, 95% CI = (−7.45, −2.52)]. In terms of reducing the ODI dysfunction score, compared with PKP combined with Cal, PKP combined with ZOL had the highest probability of being the best treatment option [MD = −9.11, 95% CI = (−14.27, −3.95)]. In terms of protecting against bone density loss, compared with PKP surgery alone, treatment with PKP combined with ZOL had the best effect [MD = 0.39, 95% CI = (0.13,0.65)]. Conclusions Based on the network meta-analysis and SUCRA rankings, this study concluded that adding teriparatide has the advantage of reducing VAS pain scores compared with PVP alone and that adding zoledronate is a more effective treatment for reducing ODI scores compared with PKP combined with Cal and preserving BMD compared with PKP alone. However, additional high-quality studies are needed to verify our findings. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=358445, identifier CRD42022358445.